2022
DOI: 10.3390/ijerph191912611
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Illness Analysis of Type 2 Diabetes Mellitus: The Findings from a Lower-Middle Income Country

Abstract: Background: Diabetes is a major chronic illness that negatively influences individuals and society. Therefore, this research aimed to analyze and evaluate the cost associated with diabetes management, specific to the Pakistani Type 2 diabetes population. Research scheme and methods: A survey randomly collected information and data from diabetes patients throughout Pakistan out-patient clinics. Direct and indirect costs were evaluated, and data were analyzed with descriptive and inferential statistics. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Among these included studies three studies were conducted in Sudan. [21][22][23] The remaining were completed in Pakistan, 19,24 Iran, 20,25 and Saudi Arabia 16,18 (two studies in each country), and one study was conducted in the UAE. 17 Only three studies calculated the overall cost of DM, including direct and indirect costs, 19,24,25 while the remaining calculated only the direct medical cost of DM.…”
Section: Resultsmentioning
confidence: 99%
“…Among these included studies three studies were conducted in Sudan. [21][22][23] The remaining were completed in Pakistan, 19,24 Iran, 20,25 and Saudi Arabia 16,18 (two studies in each country), and one study was conducted in the UAE. 17 Only three studies calculated the overall cost of DM, including direct and indirect costs, 19,24,25 while the remaining calculated only the direct medical cost of DM.…”
Section: Resultsmentioning
confidence: 99%
“…The direct costs of managing diabetes, including medication, hospitalisation and outpatient care, are substantial. Indirect costs associated with diminished productivity and disability also contribute to the economic impact 5 …”
Section: Introductionmentioning
confidence: 99%
“…Indirect costs associated with diminished productivity and disability also contribute to the economic impact. 5 However, diabetes mellitus is not just a metabolic disorder; it is also a significant risk factor for several complications and diseases, with cardiovascular disease, including stroke, coronary artery disease and peripheral arterial disease, being the common diabetes complications. 6 Hyperglycaemia, insulin resistance, dyslipidaemia and hypertension all contribute to accelerated atherosclerosis observed in diabetics, which increases their risk for myocardial infarctions, strokes and other cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…1 In accordance to the International Diabetic Foundation, around 537 million individuals possess diabetes, and it is anticipated that this number will climb to 643 million in the year 2030. 2,3 Additionally, it has been observed that the individuals with a age range of 39 and 70 years old who living in the lower income nations have a high risk of developing diabetes. There was seems to be the 6.9% of individuals in Pakistan those having diabetes, and it is estimated that such frequency will rise to approximately 8.2% in the year 2040.…”
Section: Introductionmentioning
confidence: 99%
“…There was seems to be the 6.9% of individuals in Pakistan those having diabetes, and it is estimated that such frequency will rise to approximately 8.2% in the year 2040. 2,4,5 Prior studies has looked for a correlation between the levels of glucose in the blood and the characteristics of the serum lipid profile. 6 According to the evidence of recent studies, the factor of body fat most directly responsible for the rising incidence of such a disease is one of the body composition factors.…”
Section: Introductionmentioning
confidence: 99%